Molecular Mechanisms Underlying Substance Transport, Signal Transduction, and Anti-Stress Regulation, as Well as Anti-Alkaline Regulation via Bursicon in the Cerebral Ganglion of Chinese Mitten Crab Eriocheir sinensis Under Alkaline Stress - Meiyao Wang; Jun Zhou; Jiachun Ge; Gangchun Xu; Yongkai Tang (Biology)
(1) Background: Global climate change is intensifying, and the vigorous development and utilization of saline–alkali land is of great significance. As an important economic aquatic species in the context of saline–alkali aquaculture, it is highly significant to explore the regulatory mechanisms of Eriocheir sinensis under alkaline conditions. In particular, the brain (cerebral ganglion for crustaceans) serves as a vital regulatory organ in response to environmental stress; (2) Methods: In this study, a comparative transcriptome approach was employed to investigate the key regulatory genes and molecular regulatory mechanisms in the cerebral ganglion of E. sinensis under alkaline stress. (3) Results: The results demonstrated that the cerebral ganglion of E. sinensis exhibited a positive response to acute alkaline stress. Pathways associated with signal transduction and substance transportation, such as “phagosome” and “regulation of actin cytoskeleton”, along with regulatory genes involved in antioxidation, were upregulated synergistically to maintain homeostasis under alkaline stress. Furthermore, it was discovered for the first time that bursicon plays a positive regulatory role in the adaptation of E. sinensis to alkalinity. (4) Conclusions: The present study elucidates the molecular regulatory pattern of the cerebral ganglion in E. sinensis under acute alkaline stress as well as revealing a novel role of bursicon in facilitating adaptation to alkalinity in E. sinensis, providing valuable theoretical insights into the molecular regulatory mechanisms underlying the responses of cerebral ganglia to saline–alkali environments. These findings also offer a theoretical reference for promoting the sustainable development of the E. sinensis breeding industry under saline–alkali conditions.